Determinantes sociales de la desnutrición tipo kwashiorkor en menores de 2 años de edad. tena, 2021 - Amores López, Humberto David (2022)
ABSTRACT Objective: To analyze the social determinants of Kwashiorkor-type malnutrition in patients treated at the José María Velasco Ibarra Hospital in 2021 Population and Universe: 31 patients who were hospitalized due to the diagnosis of Kwashiorkor in the pediatric service of the José María Velasco Hospital Ibarra of the city of Tena Material and Methods: the type of research carried out was correlational, retrospective and cross-sectional with data obtained directly from the medical records of patients with Kwashiorkor-type malnutrition in the statistical room of patients hospitalized in the service. of pediatrics of the General Hospital José María Velasco Ibarra. Results: From the total of 31 medical records reviewed, it is extracted that the female sex constitutes 64.5% of the total cases, 51.6% of children presented malnutrition in the first 6 months of life, within the social determinants with the highest incidence we have that the 74.2% of the patients reside in the rural area, 74.2% are indigenous, 71% of the parents completed secondary education while 58.1% of the mothers completed primary education, in relation to the family economy it is evident that they generate an income less than the basic salary 71%, agriculture constitutes 29% of the paternal occupation, 83.9% of mothers are housewives, the diagnosis of problems with the upbringing of the child was found in 71% and in relation to the number of meals, it is evident that 54.8% of the minors received from 5 to 8 meals a day. Conclusions: It is concluded that the most frequent social determinants associated with Kwashiorkor type malnutrition due to their percentage found were: residing in the rural area, indigenous ethnicity, insufficient monthly salary, a low level of education of the parents and an occupation that does not generate the necessary income. Keywords: kwashiorkor, child malnutrition, social determinants, malnutrition.